2021
DOI: 10.56381/jsaem.v1i3.67
|View full text |Cite
|
Sign up to set email alerts
|

Private Vehicle Roadworthiness in Malaysia from the Vehicle Inspection Perspective

Abstract: Vehicle defect is one of the contributing factors of road mishaps, although the magnitude of the problem is less prominent compared to human behaviour or road environment factors. What is more important is that this technical problem may find a more direct solution as opposed to human behavioural issues. This study aims to discuss common vehicle defects that probably contribute to road crashes by using Periodical Technical Inspection (PTI) database as the basis. Data was analysed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Vehicle defect is one of the factors that cause traffic accidents as mentioned by the key informant the condition of the vehicle must be taken into consideration most especially before using it all the necessary parts must be check properly like the brake, the tires, and the lights. It is supported by Solah et al (2017) found that the defects in the brake system, tires, lighting, body/paintwork, and upper body part are the most common components that contributed to road crashes Similarly, Cuerden et al (2011) investigated the effects of vehicle defects in traffic crashes The study estimated that vehicle defects are likely to be a contributing factor in around 3% of crashes in the UK. It also showed that reducing the frequency of testing of newer vehicles is likely to have adverse road safety consequences K2(Engineering)what I observe are those cars that are not maintained properly by the owner.…”
Section: A 9 Vehicle Defectmentioning
confidence: 98%
“…Vehicle defect is one of the factors that cause traffic accidents as mentioned by the key informant the condition of the vehicle must be taken into consideration most especially before using it all the necessary parts must be check properly like the brake, the tires, and the lights. It is supported by Solah et al (2017) found that the defects in the brake system, tires, lighting, body/paintwork, and upper body part are the most common components that contributed to road crashes Similarly, Cuerden et al (2011) investigated the effects of vehicle defects in traffic crashes The study estimated that vehicle defects are likely to be a contributing factor in around 3% of crashes in the UK. It also showed that reducing the frequency of testing of newer vehicles is likely to have adverse road safety consequences K2(Engineering)what I observe are those cars that are not maintained properly by the owner.…”
Section: A 9 Vehicle Defectmentioning
confidence: 98%
“…H) The EHO is responsible for ensuring that licensed e-hailing vehicles display an identification sticker provided by JPJ. Based on a database of periodic technical inspections carried out in Malaysia shows that the two most common defects in private vehicles are tire wear (or lack of tread) and structural integrity (Solah et al, 2021). Additionally, brake system failures become more prominent as a vehicle ages.…”
Section: Interdisciplinary Social Studiesmentioning
confidence: 99%
“…In addition, Keall and Newstead (2013) compared crash rates in vehicles undergoing annual inspection vs. vehicles inspected twice a year and found an 8% reduction in crash rates in the latter group after adjusting for the difference in vehicle age in the two groups (vehicles inspected annually had an average age of less than 7 years while vehicles inspected every six months were 7 years old or older). Solah et al (Solah et al, 2019) surveyed public opinion on periodic testing for private vehicles in Malaysia. Most respondents agreed on the need for roadworthiness inspections after five years of use.…”
Section: Introductionmentioning
confidence: 99%
“…In the revised version of the NAP in 2014, although there was no direct mention of the end-of life vehicle policy, the term Voluntary Vehicle Inspection (VVI) was instead inserted (Solah et al, 2017). This was seen as a softer move where the word "mandatory" was replaced with "voluntary".…”
Section: Elv Policy In Malaysiamentioning
confidence: 99%